ESG Reporting Practices and Their Role in Driving Circular Economy Innovation and Triple Bottom Line Performance among Philippine Manufacturing Enterprises: A Narrative Literature Review - Alberlyn Jo Mary L. Alegre (Future Science / FSH-PH Publications, 2026)
The study examines at how Environmental, Social, and Governance (ESG) reporting is helping mold a more responsible and sustainable future for manufacturing businesses in the Philippines. Today, businesses are no longer judged by profit alone. They are also expected to show how they protect the environment, treat people fairly, and operate with integrity. Utilizing a narrative literature review of studies published from 2015-2025, this research explores how this concept supports circular economy innovation and improves Triple Bottom Line performance, which focuses on people, planet, and profit. The review shows that government regulations, especially the SEC Memorandum Circular No. 4 (2019), greatly increased sustainability reporting among companies. While many firms now comply with reporting requirements, the actual depth of sustainability actions still differs across organizations. Evidence shows that strong ESG practices encourage circular strategies such as reducing waste, reusing materials, and designing products for longer use. These efforts are further supported by national policies like the Extended Producer Responsibility Act of 2022. But, problems remain, including limited data, uneven reporting quality, and resource constraints among smaller firms. In the nutshell, the study emphasizes that meaningful ESG reporting, combined with circular economy practices and responsible leadership can help Philippine manufacturers achieve long-term growth, resilience, and global competitiveness.